Effects of Acetaminophen and Ibuprofen on Pulpal Anaesthesia Immediately after Pulpectomy of Primary Maxillary Molars - Bahrololoomi, Zahra; Amrollahi, Narjes (Iranian Endodontic Journal, 2019)
Introduction: This study aimed to evaluate the effects of acetaminophen and ibuprofen on pulpal anaesthesia immediately after pulpectomy of primary maxillary molars. Methods and Materials: In this placebo-controlled, double-blind clinical trial, 60 children (aged 5 to 9) were referred to the Department of Pediatric Dentistry, Yazd Dental School; for primary maxillary molar pulpectomy. Local anaesthesia and analgesic drugs were used for the pre-operative stage. A five-face scale was considered to evaluate pain reaction during the pulp therapy. Pain scores were determined when the dental procedure was complete. The Kruskal-Wallis and Mann-Whitney U tests were finally used at the confidence level of 95%. Results: Use of analgesics before pulpectomy in children can reduce pain score compared to placebo group (P<0.001) and increase the effectiveness of pulpal anesthesia. Additionally, ibuprofen exhibited lower pain scores compared to acetaminophen although the difference was not statistically significant. Conclusions: Pre-operative use of ibuprofen and acetaminophen might be a useful way to achieve analgesia during pulpectomy of primary maxillary molars in children. Keywords: Acetaminophen; Analgesia; Child; Ibuprofen; Pain; Pediatric Dentistry; Pulpectom